Implementation of Lean Manufacturing to Increase Productivity in the Manufacture of Kitchen Sinks in a Metal-Mechanical Company - Avalos Ortecho, Edilberto Miguel (2023)
The application of the lean manufacturing strategy aims to reduce waste and increase the productivity of the organization in which it is applied; however, in Peru many companies in the metal-mechanical industry do not know how to implement it. The objective of the research is the application of lean manufacturing tools to increase productivity in the manufacturing of washing machines. We implemented 5S to reduce time and route waste, Kanban to standardize production based on demand and lead time, as well as the use of MRPII for its execution. In addition, it was complemented with the Jidoka philosophy to eliminate defective products. The study was carried out in a SMEs company of the metal-mechanic sector that after performing the diagnosis using VSM, productivity (0.1858 washers/H-H), defective products (9.06%) and delivery time compliance (64.67%) of stainless teel washers were identified as the main problems. The imputs found in the data collection were low delivery reliability, high defective rate and low productivity. After the application of Kanban, 5S and Jidoka, an improvement was obtained in the percentage of washers delivered on time to 100% of the orders, a reduction in the percentage of defective products to 3.23%, and an increase in productivity of 5.02%.